Profiling miRNA expression in photo-thermo-sensitive male genic sterility line (PTGMS) PA64S under high and low temperature. (2nd December 2019) - Wu, Sha; Tan, Hang; Hao, Xiaohua; Xie, Zijing; Wang, Xiaohui; Li, Dongping; Tian, Lianfu
ABSTRACT: Peiai64S (PA64S) is a photo-thermo-sensitive genic male sterile line (PTGMS), with wide application in hybrid seed production in rice ( Oryza sativa L.). Micro-RNAs are 21–24 nt, endogenously expressed small RNAs that have been characterized in various developmental stages of rice, but none have been studied with respect to the regulation of TGMS in rice. Here, we employed high-throughput sequencing to identify expression profiles of miRNAs in the anthers of PA64S at high (PA64S-H) and low temperature (PA64S-L). Two small RNA libraries from PA64S-H and PA64-L anthers were sequenced, and 263 known and 321 novel candidate miRNAs were identified. Based on the number of sequencing reads, a total of 133 known miRNAs were found to be differentially expressed between PA64S-H and PA64S-L. Target prediction showed that the target genes encode MYB and TCP transcription factors, and bHLH proteins. These target genes are related to pollen development and male sterility, suggesting that miRNA/targets may play roles in regulating TGMS in rice. Further, starch and sucrose metabolism pathways, sphingolipid metabolism, arginine and proline metabolism, and plant hormone signal transduction pathways were enriched by KEGG pathway annotation. These findings contribute to our understanding of the role of miRNAs during anther development and TGMS occurrence in rice.